Preparation of Carboxyl-End-Group Poly(methyl methacrylate) and Polystyrene with Low Polydispersity by Atom Transfer Radical Polymerization Initiated with Chloroacetic Acid - Teng, Yefang; Liu, Yueshu; Jiang, Jianguo (Asian Journal of Chemistry, 2015)
Carboxyl-end-group poly(methyl methacrylate) and polystyrene with low polydispersity were successfully prepared via atom transfer radical polymerization in bulk or in solution with chloroacetic acid as initiator and CuCl/N,N,N',N'-tetramethylethylenediamine as catalyst. The polymerizations showed the different polymerization rates depending on the feeding ratios for the atom transfer radical polymerization of both methyl methacrylate and styrene in either bulk or solution polymerization. The bulk polymerization for both monomers methyl methacrylate and styrene gave a faster polymerization rate and afforded a broader Mw/Mn of the obtained polymer. When the solvent was added into the polymerization system, the polymerization showed a moderate rate and yielded poly(methyl methacrylate) with the narrowest Mw/Mn of 1.17-1.21 and polystyrene with the narrowest Mw/Mn of 1.16-1.19, respectively. Polymerization kinetics showed that the polymerization proceeded by the normal atom transfer radical polymerization. The end groups of the well-defined poly(methyl methacrylate) and polystyrene were determined by 1H NMR.